Integration of an ARAIM algorithm in the development of an instrument approach procedure and for pre-flight operational briefing - Paternostro, S.; Moore, Terry; Hill, C.; Atkin, J.; de Maere, Geert; Morvan, Herve (2017)
Advanced Receiver Autonomous Integrity Monitoring (ARAIM) offers the opportunity to enable Global Navigation Satellite System (GNSS) receivers to serve as a primary means of navigation, worldwide, for precision approach down to Localizer Performance with Vertical guidance (LPV-200) operation. Previous produced works analysed the performance of this new technique, clearly showing the potential of ARAIM architectures to provide the Required Navigation Performance (RNP) for LPV 200. However, almost all of the studies were performed with respect to fixed points on a grid on the Earth’s surface, with full view of the sky, evaluating ARAIM performance from a geometrical point of view and using nominal performance in simulated scenarios lasting several days. In our previous work we presented the ARAIM performance in simulated operational configurations. Attitude changes from manoeuvers, obscuration by the aircraft body and shadowing from the surrounding environment could all affect the incoming signal from the GNSS constellations, leading to configurations that could adversely affect the real performance. In this paper, we continue the previous work. The new proposed algorithm integrates ARAIM performance prediction capability, considering the attitude and terrain shadowing effects, in two different scenarios: